Συλλογικές Χορηγίες στην Κέρκυρα κατά την πρώιμη λατινοκρατία. Επιγραφικά τεκμήρια - ΚΑΡΥΔΗΣ, Σπυρος (Byzantina Symmeikta, 2016)
Collective sponsorship in Corfu during the early period of the Latin rule. The epigraphic evidence This study presents inscriptions found in Corfu in four churches of the early period of the Latin occupation Of these, one is preserved in situ. Copies of three more inscriptions are preserved in the notarial archives stored in the General State Archives - Archives of Corfu. This indicates that the notarial protocols merit special attention, not only owing to valuable information relative to monuments of the Venetian period, but also relative to monuments of an earlier period: the Archives contain copies, documents and inscriptions considered by the founders of churches and monasteries as authorising their founder’s rights. The inscriptions here presented should be counted among the few recorded inscriptions from religious monuments in the Ionian Islands and confirm the thesis that the establishment and decoration of churches was supported by collective sponsorship as was the case in the Byzantine provinces and areas under Latin domination after the fourth crusade (e.g. Crete). The inscriptions also allow us to relate the orthodox religious brotherhoods that appeared during the Venetian occupation with the collective sponsorship of Church monuments as well as with the individual or collective founder’s rights.